(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Maria S. Balikova (Moscow, Russian Federation) The most significant work of Merezhkovsky-critic – a treatise «L. Tolstoy and Dostoevsky» – is explored. The author’s examples and parallels from the sphere of the fine arts are analyzed. Penetrating the treatise comparisons of Russian writers with the creators of paintings and sculptures, including masters of the Renaissance, are discussed. It is shown that the Merezhkovsky’s statement that there is a need for a synthesis of creative aspirations of Tolstoy and Dostoevsky is the basis of the critic-philosopher’s thinking about the movement of Russian culture from Pushkin’s lost harmony by overcoming the antithesis of flesh and spirit, paganism and Christianity, to their conscious, deep and final connection and, ultimately, to the worldwide religious revival. Key words: Merezhkovsky, the Renaissance, the fine arts, Russian literature, religion, the synthesis of phenomena. DOI 10.23683/1995-0640-2017-3-12-18